Challenges of Financing Agricultural Investment Evidence From Gambella Region, Ethiopia - Chuol Jock Ruey; Ganfure Tarekegn Kistana; Eshetu Yadecha (Faculty of Economics, Universitas Sriwijaya, 2020)
The aim of this paper was to assess the agricultural investment financing challenges in Gambella city administration and Itang special Woreda, Ethiopia. To achieve the objectives, data were collected from both primary using questionnaires and secondary sources from annual reports, manuals, and performance reports. Explanatory research design was used and the 215 sample were selected using stratified random sampling technique from workers of DBE, investment agency and investors of Gambella region. The data were analyzed using SPSS version 20 to run both descriptive and multiple liner regression result. Accordingly, the major challenging factors are the low investment return, farm risk, security issues, lending procedures, farm size, distant of investor’s farm from lender, poor infrastructure, lack of technical capacity, farm age and budget failure with their respective proportion. The correlation matrix result showed that here is no multicollinearity problem existing among explanatory variables. Regression also revealed that all the explanatory variables with exception of budget failure and lending procedures have significant challenging effects on financing agricultural investment. Finally, the research recommended that diversified sources of finance for agricultural investment should be established, training programs on performance issues, irrigation in response to drought, agricultural technical capacity, and infrastructure facilities are needed, stable security and return of loan amount must be seriously dealt with, and measures like strong monitoring and evaluation need to be put into practice.